Transformation optofluidics for large-angle light bending and tuning - Zheludev, Nikolay I. (2013)
Transformation optics is a new art of light bending by designing materials with spatially variable parameters for developing wave-manipulation devices. Here, we introduce a transformation optofluidic Y-branch splitter with large-angle bending and tuning based on the design of a spatially variable index. Differing from traditional splitters, the optofluidic splitter is achieved in an inhomogeneous medium by coordinate transformation. The designed bidirectional gradient index (GRIN) distribution can be achieved practically by the convection-diffusion process of liquid flowing streams. The transformation optofluidic splitter can achieve a much larger split angle with little bend loss than the traditional ones. In the experiments, a large tunable split angle up to 30° is achieved by tuning the flow rates, allowing optical signals to be freely transferred to different channels. Besides the symmetrical branch splitting, asymmetrical Y-branch splitting with approximately equal power splitting is also demonstrated by changing the composition of the liquids. The optofluidic splitter has high potential applications in biological, chemical and biomedical solution measurement and detection.